Synthesis and application of cationized cellulose for adsorption of anionic dyes. (2022) - Mhlongo, Jessica Tsakani; Dlamini, Mbongiseni Lungelo; Nuapia, Yannick; Etale, Anita
Abstract: Synthetic dyes are commonly used in paper, printing, leather, food, and textile industries. Dyes are non-biodegradable and unstable in the environment causing allergies and hypersensitivity in humans even at low concentrations. Adsorption process is a simple and reliable popular method as it has been extensively used on a variety of contaminants. The availability and use of low-cost adsorbents such as natural cellulose makes it more favorable. In this study, cationized hemp cellulose was used as an adsorbent for the removal of methyl orange (MO), and sunset yellow (SY) from aqueous solutions. The cellulose was extracted from hemp fibers by alkali treatment using 4 %wt NaOH and bleached using 1.7% NaOCl2 in acetate buffer solution. Glycidyl trimethylammonium chloride (GTMAC) was used as a cationizing agent to functionalize cellulose (GT-cellulose). For adsorption studies, the influence of pH, adsorbent dosage, initial dye concentration, contact time, and temperature were investigated using batch experiments. After modification, cellulose showed enhanced adsorption capacity for removal of anionic dyes from aqueous solution. The equilibrium adsorption isotherm data were best described by Langmuir model. The maximum adsorption capacity for MO and SY onto GT-cellulose were found to be 76.9 mgg −1 and 44.9 mgg −1 respectively. The adsorption kinetics were best fit with pseudo-second order for both anionic dyes. The thermodynamic study showed that the adsorption processes for MO and SY were both endothermic and spontaneous in nature. From the resulted, cationized cellulose adsorbents could be effectively applied for removal of anionic dye from wastewater.